Akhlak Menurut Syaikh Taqiyuddin An-Nabhani Dalam Kitab Nidzamul Islam - Siregar, Mariani (Khazanah : Journal of Islamic Studies, 2024)
The process of forming morals (akhlak) is a necessity for every Muslim student. Discussions about morals never stop and grow old from time to time, even among the ulama (Muslim Scholars). Because there are always changes in the realities of life among Muslims, this causes behavior to also reflect changes. However, even though many have provided views on morals, the author still feels the need to adopt a unique and distinctive theory about morals. Not all scholars' opinions view moral issues the same. As understood by Shaykh Taqiyuddin An-Nabhani, according to him, morals are the fruit of belief and practice of Islamic law. And not just morals without the right foundation or direction. Moral education is also a provision in the formation of syaksiyah Islamiyah (Islamic personality), which is the identity of a typical and unique Muslim student. The application of morals that are straight, noble and in accordance with Islamic teachings will ground the mission of the revelation of Islam through the Prophet Muhammad, namely as rahmatan lil'alamin and the perfecter of morals for humans. So it can be concluded from his view, that the case cannot be separated from the faith and the Shari'a.